Comparing the effects of isocaloric oral and i.v. application of nutrient solutions on olfactory functioning - Bachlechner, Stephan; Denzer-Lippmann, M.; Wielopolski, Jan; Fische, Mr; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Münch, Georg; Kornhuber, Johannes; Thürauf, Norbert (2016)
EVALuna2:33154

Effect of oral bolus versus sustained release application of nutrient solution on olfaction - Denzer-Lippmann, Melanie; Bachlechner, S.; Wielopolski, Jan; Fischer, M.; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Münch, Gerald; Kornhuber, Johannes; Thürauf, Norbert (2016)
EVALuna2:33155

Effects of different isocaloric oral nutrient solutions on olfactory functioning, hunger and food craving - Thürauf, Norbert; Denzer-Lippmann, Melanie; Bachlechner, Stephan; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Münch, Gerald; Kornhuber, Johannes (2017)
EVALuna2:33148

Grehlin concentrations correlate with hunger and craving ratings following oral ingestion of macronutrients - Thürauf, Norbert; Bachlechner, Stephan; Denzer-Lippmann, Melanie; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Muench, Gerald; Kornhuber, Johannes (CHEMICAL SENSES, 2019)
CRIS-Team WoS Importer:2019-03-26

Physical activity and energy expenditure during depressive episodes of major depression - Wielopolski, Jan; Reich, Karin; Clepce, Marion; Fischer, Marie; Sperling, Wolfgang; Kornhuber, Johannes; Thürauf, Norbert (Journal of Affective Disorders, 2015)
Recent data suggest a substantial association between physical activity and depressive symptoms, but there is a lack of research evaluating the physical activity levels in patients suffering from unipolar depression across different stages of disease in an objective way. The aim of the present pilot study was to objectively examine physical activity levels of this patient group compared to healthy controls.Physical activity performance of 19 patients with major depressive episode and 19 healthy controls was assessed at three different time points using a multisensory armband device (SenseWear® Pro3 Armband) and was reported as total energy expenditure (TEE), active energy expenditure (EE), metabolic equivalents (METs), physical activity (PA) and time of lying down (LD), in each case over 24h.Over all measurements, depressive patients presented a significantly lower mean TEE and EE over 24h. Moreover, the patient group showed significantly shorter duration of PA and lower average MET over 24h. When depressive symptoms abated, physical activity parameters significantly increased in the patient group. Correlation analyses demonstrated a significant relation between depressive status/anhedonia and parameters of physical activity, especially in healthy subjects.Results represented valid data for inpatients only.Acute unipolar depression was associated with a significantly lower level of physical activity and showed a significant increase in parallel to clinical improvement. Electronic monitoring of physical activity may be an additional tool for evaluating and controlling therapeutic effects.
EVALuna2:23724

The Effects of a Normal Rate versus a Slow Intervalled Rate of Oral Nutrient Intake and Intravenous Low Rate Macronutrient Application on Psychophysical Function - Two Pilot Studies - Denzer-Lippmann, Melanie; Bachlechner, Stephan; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Muench, Gerald; Kornhuber, Johannes; Thürauf, Norbert (Frontiers in Psychology, 2017)
Stomach distension and energy per time are factors influencing satiety. Moreover, different rates of nutrient intake induce different stomach distension. The goal of our studies was to elucidate the influence of different oral rates of nutrient intake (normal rate versus slow intervalled rate; study I) and intravenous low rate macronutrient application (protein, carbohydrate, fat) or placebo (study II) on psychophysical function. The pilot studies investigated the effects of 1) study I: a mixed nutrient solution (1/3 protein, 1/3 fat, 1/3 carbohydrates) 2) study II: intravenous macronutrient infusions (protein, carbohydrate, fat) or placebo on psychophysical function (mood, hunger, food craving, alertness, smell intensity ratings and hedonic ratings) in human subjects. In study I 10 male subjects (age range: 21-30 years) completed the study protocol participating in both test conditions and in study II 20 male subjects (age range: 19-41 years) completed the study protocol participating in all test conditions. Additionally, metabolic function was analyzed and cognitive and olfactory tests were conducted twice starting 100 min before the beginning of the intervention and 240 min after. Psychophysical (mood, hunger, fat-, protein-, carbohydrate-, sweets- and vegetable-craving), alertness and metabolic function tests were performed seven times on each examination day. Greater effects on hunger and food cravings were observed for normal rate of intake compared to slow intervalled rate of intake and intravenous low rate macronutrient application. Our findings potentially confirm that volume of the food ingested and a higher rate of energy per time contribute to satiety during normal rate of food intake, while slow intervalled rate of food intake and intravenous low rate macronutrient application showed no effects on satiation. Our results motivate the view that a certain amount of volume of the food ingested and a certain energy per time ratio are necessary to reduce hunger and food craving.
EVALuna2:33741
Keywords: food ingestion; food intake; rate of food intake; psychophysical function; food craving; parenteral food administration; parenteral food intake

The Effects of Different Isocaloric Oral Nutrient Solutions on Psychophysical, Metabolic, Cognitive, and Olfactory Function in Young Male Subjects - Bachlechner, Stephan; Denzer-Lippmann, Melanie Y.; Wielopolski, Jan; Fischer, Marie; Büttner, Andrea; Dörfler, Arnd; Schöfl, Christof; Muench, Gerald; Kornhuber, Johannes; Thürauf, Norbert (Frontiers in Psychology, 2017)
Food intake influences human cognition, olfaction, hunger, and food craving. However, little research has been done in this field to elucidate the effects of different nutrients. Thus, the goal of our study was to investigate the effects of oral ingestion of different nutrient solutions on olfactory, cognitive, metabolic and psychophysical function. Twenty healthy men participated in our study employing a double-blind, cross-over, repeated measurement design. Participants were tested on four different study days. Each day participants received, in randomized order, one of three isocaloric (protein, carbohydrate or fat 600 kcal, 1,500mL) solutions or a placebo. Olfactory and cognitive tests (monitoring only) were conducted three times, i.e., 60min before the beginning of nutrient intake, following oral ingestion of the solution and 60, and 240min after. Psychophysical and metabolic function tests (active grehlin, desacyl ghrelin, insulin, glucagon, glucose, triglyceride, urea) were performed 7 times on each examination day (observation period: -60min, 0 = solution intake, +60, +120, +180, +240, and +300min). Ratings of hunger and food craving significantly differed over the observation period with lowest ratings following application of the protein solution. Highest ratings of craving were found following placebo intake. We further observed a significant positive correlation of active grehlin with hunger and fat, protein and sweets craving for each nutrient solution. Active grehlin significantly correlated with carbohydrate craving for carbohydrate and fat solution and with vegetable craving for fat solution only. Hunger hormone levels, hunger and food craving ratings demonstrated that the hierarchical order that appears in satiating efficiencies of isovolumetric-isocaloric ingested macronutrients is protein > fat > carbohydrate. Our study reveals that the type of nutrient exerts a significant influence on metabolic parameters, hunger and food craving.
Keywords: food ingestion; food intake; oral intake; olfaction; psychophysical function

The psychophysical assessment of odor valence: does an anchor stimulus influence the hedonic evaluation of odors? - Clepce, Marion; Neumann, Konrad; Martus, Peter; Nitsch, Marie; Wielopolski, Jan; Koch, Anna Maria; Kornhuber, Johannes; Reich, Karin; Thürauf, Norbert (Chemical Senses, 2014)
Olfactory stimuli are experienced primarily in terms of their hedonic tone and the assessment of olfactory hedonic estimates is a prevalent task in scientific and industrial contexts. However, measuring conditions are poorly standardized. Our study aims to fill this gap, focusing on the influence of anchor stimuli on olfactory hedonic evaluations, frequency of anchor presentation, and temporal stability of results. In n = 31 subjects, hedonic estimates for the 16 odors of the Sniffin' Sticks identification task were assessed on a visual analog rating scale under 4 measuring conditions (nonanchor, pleasant anchor, neutral anchor, unpleasant anchor). To test for stability over time, n = 10 subjects were reassessed 2, 4, and 6 months after original testing. To analyze for possible effects of single versus repeated anchor presentation, n = 15 subjects were retested 2 months after the original session in a multiple anchor presentation format. Statistical analysis revealed significant differences between the 4 anchor conditions, thus highlighting the necessity of specifying assessment methods in scientific research. No significant differences between timepoints were observed, indicating a high temporal stability of olfactory hedonic evaluations, especially from timepoint T2 onward. No overall significant effects of single versus multiple anchor presentation were detected. Findings might help to further standardize testing procedures.
EVALuna2:23574